THE RELATIONSHIP BETWEEN ORGANIZATIONAL CULTURE AND COMMITMENT TO ORGANIZATION CITIZENSHIP BEHAVIOR AT PRESTISA (PT KAYA RAYA TURUN TEMURUN) - Naiborhu , Joseph Rivan; Anggraini, Nenny (Universitas Kristen Indonesia, 2021)
Organizational Citizenship Behavior (OCB) is prosocial behavior or extra precautions that exeed a specified discription of the role within the organization or company. In this study, the issues to be discussed is how is the relationship between organizational culture, organizational commitment, and Organizational Citizenship Behavior. The research was conducted at the PT PRESTISA, Jakarta. The purpose of this study was to determine the relationship of organizational culture and organizational commitment of Organizational Citizenship Behavior (OCB). This research is descriptive-correlational by as many as 30 employees, and data were analyzed using Spearmen Rank Correlation and multiple correlation Pearson Product Moment. The result of this study was indicated that 1) there is a positive and significant relationship between Organizational Culture and OCB of employees at PT PRESTISA. It is shown by t (3,348) is greater than t table (2,048), 2) there is a positiveand significant relationship between Organizational Commitment and OCB of empoyees at PT PRESTISA. It is shown by t (2,483) is greater than table (2,048), 3) there is a positive and significant relationship between Organizational Culture, Organizational Commitment, and OCB of employees at PT PRESTISA. It is shown by F (7,958) is greater than F table (3,354). Keyword : organizational culture, organizational commitment, organizational citizenship behavior (OCB)